Mapping the QTL and tagging yield traits in bitter gourd (Momordica charantia L.) using microsatellite markers. (January 2023) - Lavale, Shivaji Ajinath; Mathew, Deepu; Pradeepkumar, T.; Joseph John, K.; Joseph, Jiji
Abstract: A genetic map spanning 1287.99 cM across 11 linkage groups was constructed following the segregation of microsatellite markers in an F2:3 mapping population generated by crossing high yielding cultivar Priyanka ( M. charantia var. charantia ) and M. charantia var. muricata accession IC634896. QTLs were identified for 24 traits including yield-contributing traits such as fruit length, breadth, weight and number, flesh thickness, node number and days taken for first pistillate flower emergence, numbers of staminate and pistillate flowers, and other seed-, vine- and leaf-related traits. Inclusive Composite Interval Mapping (ICIM) has revealed 60 QTLs on seven chromosomes, including 37 major QTLs with LOD values ranging from 3.1 to 15.2, explaining 1.8–35.9% phenotypic variation (PVE%). Twenty three QTLs for fruit traits (LOD 3.1 to 7.6, PVE% 5.5 to 35.9), 13 for flower traits (LOD 3.1 to 15.2, PVE% 7.0 to 26.0), seven each for seed and leaf traits (LOD 3.2 to 10.8 and 3.5 to 6.5, PVE% 5.6 to 26.3 and 3.2 to 15.8, respectively), 10 for vine traits (LOD 3.2 to 8.7, PVE% 1.8 to 17.6), were identified. Single marker analysis identified 129 hits for the marker-trait association (LOD >3.0, PVE% 11.62 to 29.34). Using the least and best performing F2:3 plants, markers S13, KAUBG_5 and KAUBG_11 were validated for co-segregation with fruit breadth, first pistillate flower node, and number of pistillate flowers and fruits per plant, respectively. QTL map and trait-tagged markers identified in this first microsatellite-based linkage map will significantly assist in marker assisted breeding in bitter gourd. Highlights: SSR-based QTL mapping in F2:3 population of M. charantia var. charantia x M. c. muricata . Linkage map spanned 1287.99 cM across 11 LGs with 85 SSR markers. Sixty QTLs for 24 yield traits with LOD scores 3.1–15.2, explaining 1.8–35.9% PVE. Co-segregating alleles for important fruit and flower traits were identified by SMA. Allelic markers for earliness, fruit breadth and fruit number were validated.